2013
DOI: 10.1038/cddis.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic evaluation of the signaling events regulating curcumin-mediated chemosensitization of breast cancer cells to 5-fluorouracil

Abstract: 5-Fluorouracil (5-FU) is the first rationally designed antimetabolite, which achieves its therapeutic efficacy through inhibition of the enzyme thymidylate synthase (TS), which is essential for the synthesis and repair of DNA. However, prolonged exposure to 5-FU induces TS overexpression, which leads to 5-FU resistance in cancer cells. Several studies have identified curcumin as a potent chemosensitizer against chemoresistance induced by various chemotherapeutic drugs. In this study, we report for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 47 publications
(69 reference statements)
6
82
0
Order By: Relevance
“…Activation of the AKT pathway in 5-FU chemoresistant ESCC cells and tumor xenografts has been reported (34,35), and a recent study showed that AKT is upstream of thymidylate synthase in the 5-FU signaling events (36). Therefore, our data showing significant suppression of p-AKT and thymidylate synthase by cixutumumab treatment suggest that inhibiting the PI3K/AKT pathway and thymidylate synthase expression may be the mechanisms by which cixutumumab helps cancer cells overcome 5-FU resistance.…”
Section: Discussionmentioning
confidence: 50%
“…Activation of the AKT pathway in 5-FU chemoresistant ESCC cells and tumor xenografts has been reported (34,35), and a recent study showed that AKT is upstream of thymidylate synthase in the 5-FU signaling events (36). Therefore, our data showing significant suppression of p-AKT and thymidylate synthase by cixutumumab treatment suggest that inhibiting the PI3K/AKT pathway and thymidylate synthase expression may be the mechanisms by which cixutumumab helps cancer cells overcome 5-FU resistance.…”
Section: Discussionmentioning
confidence: 50%
“…The co-administration of 5-FU and curcumin results in inhibition of DNA synthesis in MDA-MB-231 cells and enhanced LD 50. 120 A synergistic administration of EGCG and curcumin results in inhibition on cell growth and induced apoptosis in MCF-7 cells that are both doxorubicin (DOX) sensitive and resistant. Qian-Mei et al, 121 studied the combination of curcumin and mitomycin C (MMC) on a MCF-7 xenograft mouse model and observed an increase in apoptosis and inhibition of tumour growth via the ERK pathway.…”
Section: The Effect Of Curcumin On Various Breast Cancer Signaling Pamentioning
confidence: 99%
“…However, studies indicate that 5-FU treatment induces TS expression, which might lead to chemoresistance [26,27]. The low level of TS is generally thought to sensitize cells to 5-FU.…”
Section: Introductionmentioning
confidence: 98%